2011
DOI: 10.1002/jcb.22962
|View full text |Cite
|
Sign up to set email alerts
|

Combined activin A/LiCl/Noggin treatment improves production of mouse embryonic stem cell‐derived definitive endoderm cells

Abstract: Induction of definitive endoderm (DE) cells is a prerequisite for the whole process of embryonic stem (ES) cells differentiating into hepatic or pancreatic progenitor cells. We have established an efficient method to induce mouse ES cell-derived DE cells in suspension embryonic body (EB) culture. Similar to previous studies, mouse ES cell-derived DE cells, which were defined as Cxcr4(+) c-Kit(+) , Cxcr4(+) E-cadherin(+) cells or Cxcr4(+) PDGFRa(-) cells, could be induced in the serum-free EBs at Day 4 of induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
2
29
1
1
Order By: Relevance
“…Previous studies reported that the TGF-␤/Smad, Wnt/␤-catenin, and FGF signaling pathways can regulate the formation of the definitive endoderm (2,4,7). To test which signal that activates ER stress is associated with definitive endoderm differentiation, we performed Western blotting assays with the whole lysate from ESCs treated with TG/TM and found an active translation of Bip, which was not evident in the control cultures (Fig.…”
Section: Tgf-␤/smad Signaling In the Definitive Endodermal Specificatmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies reported that the TGF-␤/Smad, Wnt/␤-catenin, and FGF signaling pathways can regulate the formation of the definitive endoderm (2,4,7). To test which signal that activates ER stress is associated with definitive endoderm differentiation, we performed Western blotting assays with the whole lysate from ESCs treated with TG/TM and found an active translation of Bip, which was not evident in the control cultures (Fig.…”
Section: Tgf-␤/smad Signaling In the Definitive Endodermal Specificatmentioning
confidence: 96%
“…Several signaling pathways and cascades of transcription factors have been reported to have roles in the induction and specification of the definitive endoderm at different stages of development (2)(3)(4)(5)(6). TGF-␤ signaling has been thought to be essential for the formation of the definitive endoderm (7,8).…”
mentioning
confidence: 99%
“…Distinct levels and combinations of signals through pathways such as Wnt, Nodal/TGFβ, BMP, and FGF/MAPK direct the exit from pluripotency and govern the induction of lineage-specific transcription factors, which ultimately dictate cell type. For example, high flux through the Wnt and Nodal pathways cooperatively engages master transcriptional regulators of endoderm formation, including Sox17 and GATA4 (Gadue et al 2006;Grapin-Botton and Constam 2007;Li et al 2011a). These factors subsequently induce more terminal differentiation makers, such as Hnf4α and albumin, to generate the specialized cells associated with this germ layer (Bossard and Zaret 1998;Kanai-Azuma et al 2002).…”
mentioning
confidence: 99%
“…mESC lines E14tg2a, 46C, HDAC1 lox/lox , Rosa26Cre-ER mESC and HDAC2 lox/lox , Rosa26Cre-ER mESC were used in this study and cultured in feeder-free medium 64 . Monolayer culture for neural differentiation was performed as previously described 40 .…”
Section: Methodsmentioning
confidence: 99%